Komunitaryzm – recepta na współczesne rozłamy społeczne? - Kołodziejczyk, Joanna (2019)
Communitarianism is a trend that ennobles the importance of communities in human life. It focuses on the individual as a social being that develops his potential through correlations in social groups. Most importantly, the communitarians believe that the group can achieve much more for the common good than the individual actions. Respect for tradition and basic moral values is to build bonds between citizens that foster the development of a democratic civil state. Communitarianism denies the currently promoted liberalism and individualism due to the diminishing sense of individual's commitment to the community and in the future, as expected by the breakdown of society. I will try to answer the question whether this is a trend that gives ready solutions in connection with what is often more frequent social splits in Europe and in the world. Maybe communitarianism should be disseminated in the modern world because of the benefits that it can bring in the future
Keywords: komunitaryzm; liberalizm; wspólnota